2019
DOI: 10.3233/jad-181108
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Approach of Early-Onset Dementia with Negative Family History: Implications from Two Cases of Early-Onset Alzheimer’s Disease with De Novo PSEN1 Mutation

Abstract: For early-onset Alzheimer's disease (EOAD) cases with unclear family history, most cases are sporadic. Some cases are positive in genetic findings, that is, either incomplete penetrance or de novo mutation. We aimed to focus on EOAD cases with de novo mutations. Case reports and literature review were performed. The implication for diagnostic approach of early-onset dementia with negative family history was developed. We reported two Chinese EOAD cases with de novo mutations. The genotype PSEN1 G206S appeared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…We report a case presenting with levodopa-responsive EOP and MCI with a de novo mutation (p.M233V) in PSEN1. This mutation has been previously reported in patients with complex phenotypes, including cognitive impairment, movement disorders, and neuropsychiatric disorders [4][5][6][7]. In most of these cases, the initial symptom was cognitive impairment (one with combined cerebellar manifestation), while our patient was characterized by a combination of parkinsonism and cognitive impairment.…”
Section: Discussionsupporting
confidence: 49%
“…We report a case presenting with levodopa-responsive EOP and MCI with a de novo mutation (p.M233V) in PSEN1. This mutation has been previously reported in patients with complex phenotypes, including cognitive impairment, movement disorders, and neuropsychiatric disorders [4][5][6][7]. In most of these cases, the initial symptom was cognitive impairment (one with combined cerebellar manifestation), while our patient was characterized by a combination of parkinsonism and cognitive impairment.…”
Section: Discussionsupporting
confidence: 49%
“…We report a case of a 35-year-old woman with significant deterioration in psychomotor functioning, depression, and catatonic features, who was found to have the early-onset dementia-causing PSEN1 mutation. Early-onset AD occurs prior to 65 years of age [ 2 , 3 ]. Pathologically, it is characterized by the accumulation of intracytoplasmic neurofibrillary tangles and amyloid deposition in the parenchyma and blood vessels [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in this gene can be associated with onset of AD as early as the late 20s, with most people with pathogenic mutations developing AD before the age of 60 years 45,46 . Although most cases are familial, de novo PSEN1 pathogenic variants have also been found in people with sporadic EOAD, where further testing showed that neither parent had the variant, and therefore, it likely occurred for the first time in the affected individual at conception 8–18,47 …”
Section: Admentioning
confidence: 99%